Freshwater ecology : concepts and environmental applications of limnology - Dodds, Walter K. [ (Walter Kennedy)] , 1958-; Whiles, Matt R. (Academic Press, 2010)
Covers applied and basic aspects of limnology, with emphasis on wetlands and reservoirs. This text takes a synthetic approach to ecological problems, teaching students how to handle the challenges faced by contemporary aquatic scientists. It offers coverage of climate change, ecosystem function, hypertrophic habitats and secondary production